2014
DOI: 10.14257/ijca.2014.7.4.38
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neural Network and Fuzzy Logic Control for Nonlinear Model of Two Link Rigid Manipulator

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…To sum up, FLC shows better control than the NARMA-L2 method and PID with less MSE for the pitch angle. However, the PID controller shows a better response to the yaw angle in comparison to the FLC and NARMA-L2 These findings are in agreement with the study conducted by Singh & Panjwani [7] where it was indicated that the use of FL method had an improved effect on the nonlinear two links of a rigid manipulator.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…To sum up, FLC shows better control than the NARMA-L2 method and PID with less MSE for the pitch angle. However, the PID controller shows a better response to the yaw angle in comparison to the FLC and NARMA-L2 These findings are in agreement with the study conducted by Singh & Panjwani [7] where it was indicated that the use of FL method had an improved effect on the nonlinear two links of a rigid manipulator.…”
Section: Resultssupporting
confidence: 90%
“…Singh and Panjwani [7] compared the effectiveness of fuzzy logic and NARMA-L2 controllers to control two links of a rigid manipulator. This application mimics the human upper arm which is known as a robotic arm.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations